AL-KHULUW (KOMPENSASI PELEPASAN HAK) ANTARA TEORI, PRAKTIK, DAN SOLUSI EKONOMI KONTEMPORER - Mustofa Mustofa; Manshur Idris (LP2M Universitas Ibrahimy, 2018)
Economy continues to grow rapidly especially supported by the advancement of science and technology which increasingly encourages the creation of economic practices that have never happened in the past, the distance between one country and another is getting closer, so it is possible to do transactions between countries both individually and institutionally. In the fields of trade, investment, export-import, stock exchange, leasing, buying and selling, bonds and almost all developing economic practices require answers and legal solutions for Muslims so that their implementation is in accordance with the guidelines of Islamic law, for the sake of the realization of the benefit and goodness of the world and the hereafter. Al-Khuluw (releasing rights) is one of the economic practices developed today in the lease agreement. This practice has developed in several Islamic countries, such as Egypt, Morocco, Iraq and Syria. Al-Khuluw practice is a contract in which the land owner, house or shophouse asks for a sum of money outside the rental price according to the agreement as compensation for him who has rented the place to the tenant or the owner gives money outside the rental price according to the tenant to cancel the contract in the middle the road due to certain reasons, or the first tenant rents his place to the second tenant by accepting money outside the rental price according to the agreement as compensation for the first tenant.